Tolerance of Different Cowpea Cultivars Subjected to Irrigation with Saline Waters - Silva Júnior, José Valdenor; Bezerra, Antônio Aécio de Carvalho; Silva, Everaldo Moreira; Souza, Wesley dos Santos; Cunha, Jenilton Gomes; Costa, Romário Martins (Fronteira: Journal of Social, Technological and Environmental Science, 2025)
Assuming that irrigation water salinity influences the growth and yield of cowpea plants, this study aimed to evaluate the effect of irrigation water salinity levels on the morphological and production traits of three cowpea cultivars. The experiment consisted of five salinity levels of irrigation water: (0.01, 1.41, 2.81, 4.21 and 5.61 dS m-1), three cultivars (BRS Tumucumaque, BRS Guariba, and BRS Imponente) and two periods of cultivation. A completely randomized block design was adopted in a split-split plot arrangement with four replications. The following parameters were evaluated: stem diameter (SD), plant height (PH), number of lateral branches (NLB), pod length (PL), number of grains per pod (NGP), ten-pod weight (TPW), number of pods per plant (NPP), 100-grain weight (GW) and grain yield. The data were subjected to analysis of variance by applying the F-test at 5% probability. Regression analysis was performed for the quantitative factor. There was a significant effect of the interaction between factors on all variables analyzed. The increase in irrigation water salinity reduces the morphological performance and yield of the cowpea cultivars BRS Tumucumaque, BRS Guariba, and BRS Imponente. However, the cultivar BRS Tumucumaque was the most tolerant to the negative effects resulting from increased irrigation water salinity.